O uso da fotobiomodulação o no tratamento da xerostomia da covid longa: estudo clínico, randomizado, cego, controlado - Oliveira, Susyane Vieira de (2024)
Long COVID, according to the World Health Organization (WHO), is a clinical syndrome that originates from the acute SARS-CoV-2 infection, persists for at least three months after the onset of COVID-19, and cannot be explained by an alternative diagnosis. It is a multisystem condition involving various symptoms such as pain, fatigue, and changes in the oral cavity. Salivary secretion abnormalities were reported by 2 to 40% of acute COVID survivors monitored for 28 to 230 days, demonstrating that xerostomia can be found in Long COVID cases and its persistence. Initial therapeutic approaches for xerostomia include behavioral and adaptive measures to control symptoms, prevent complications, and reduce hyposalivation when present. Photobiomodulation has been widely and successfully used in the treatment of xerostomia of other etiologies. The objective of this clinical, prospective, randomized, blind, controlled study was to evaluate the effects of a photobiomodulation protocol on long COVID xerostomia, oral functionality and quality of life. Ten patients were randomized into one of two groups: the first, participants treated with a continuous therapeutic LED light protocol (227 mW/cm2, 660 nm wavelength). The second group, participants treated with a placebo light. The light was administered extraorally bilaterally on the topography of the parotid, submandibular, and sublingual glands 2 times per week for 6 weeks. Pre- and post-treatment assessments were carried out using the SF-36 Quality of Life scale, sialometry with and without stimulation, the Oral Health Impact Profile (OHIP-14), Xerostomia Inventory (XI), and the Functional Independence Measure (FIM). The results obtained did not show statistically significant differences between the treatment and placebo groups compairing the pre- and post-treatment periods for the studied variables: Salivary pH, Salivary Flow (stimulated and unstimulated), SF-36 and MIF. However, it found positive results regarding the improvement in relation to question 7 of domain 4 (“Your diet was impaired") of the OHIP-14, and in questions 3 (“I get up at night to drink”) and 4 (“I have difficulty eating dry foods”) of XI, comparing the pre-intervention moments with the post-intervention moment in the PBM group, suggesting that there may be a tendency for improvement in the PBM group greater than that in the placebo group.